1996
DOI: 10.1021/bk-1996-0655.ch023
|View full text |Cite
|
Sign up to set email alerts
|

Possible Applications of Cellobiose Oxidizing and Other Flavine Adenine Dinucleotide Enzymes in the Pulp and Paper Industry

Abstract: Properties of the cellobiose oxidizing enzymes cellobiose:quinone oxidoreductase (CBQ) and cellobiose dehydrogenase (CDH) are outlined and comparison made with veratryl alcohol oxidase (VAO). Their importance for lignin and cellulose degradation by white-rot fungi is discussed as well as their possible use for applications in the pulp and paper industry. These applications include iron(III) and quinone reduction, studies on yellowing of paper, and (ligno)cellulose fibre characterization. Shortening of fibres a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Several authors suggested that CDH could be used as part of an enzyme complex to modify or break down cellulose and lignin in the pulp and paper industry [131]. The suggestion was to use it similar to other ligninolytic enzymes in the presence of complexed iron [112].…”
Section: Enzymatic Treatment Of Paper Pulpmentioning
confidence: 99%
“…Several authors suggested that CDH could be used as part of an enzyme complex to modify or break down cellulose and lignin in the pulp and paper industry [131]. The suggestion was to use it similar to other ligninolytic enzymes in the presence of complexed iron [112].…”
Section: Enzymatic Treatment Of Paper Pulpmentioning
confidence: 99%
“…At the dislocated region, fibre cell wall is loosened up resulting in a change of MFA [101] and separation of microfibrils. Therefore, the accessibility of cell wall elements at the dislocations to the chemical hydrolysis by the acids, enzymes and other agents is increased [96,31,32]. Fibre wall thickness 10 −06 Micro structure 10 −07 10 −08 Ultra structure 10 −09 10 −10 Molecular structure Figure 2.11: Slip plane and compression failure adapted from [227,125] Fibre wall deformations has been observed and characterised by polarised light [186,227], stains [118], enzymes [31], swelling agents [209] and acid cleavage [29].…”
Section: Weak-points In Fibre Wallmentioning
confidence: 99%
“…Therefore, the accessibility of cell wall elements at the dislocations to the chemical hydrolysis by the acids, enzymes and other agents is increased [96,31,32]. Fibre wall thickness 10 −06 Micro structure 10 −07 10 −08 Ultra structure 10 −09 10 −10 Molecular structure Figure 2.11: Slip plane and compression failure adapted from [227,125] Fibre wall deformations has been observed and characterised by polarised light [186,227], stains [118], enzymes [31], swelling agents [209] and acid cleavage [29]. Fibre wall deformations with reference to wood fibres has been reviewed by Wilkins [238] whereas the review from Nyholm et al [166] was focused on pulp fibres.…”
Section: Weak-points In Fibre Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the hydrolytic cellulases, extracellular oxidative enzymes apparently are involved in cellulose degradation by P. chrysosporium and, presumably, other white rot fungi (3,15). Cellobiose dehydrogenase (CDH) is an extracellular enzyme containing two domains; one domain contains flavin adenine dinucleotide, and the other domain contains a heme (18,19).…”
mentioning
confidence: 99%